Development Of Sangkumpal Bonang Traditional Market Padang Sidempuan City - Tambunan Julpan; Abdi Sugiarto; Abdiyanto (Yayasan Multidimensi Kreatif, 2024)
The market is a facility that accommodates people's activities in shopping to meet their daily needs. Padang Sidempuan City has many markets, one of which is the Sangkumpal Bonang Traditional Market which is one of the traditional markets in Padang Sidempuan City that has not been properly facilitated. The condition of the Sangkumpal Bonang Traditional Market is now far from the standard of a traditional market. The need for special development in the Development of the Sangkumpal Bonang Market in accordance with traditional market standards. This research aims to determine the direction of the development of the Bonang Sangkumpal Market in the City of Padang Sidempuan City. The method used in this study uses the Qualitative Descriptive Analysis Method, and SWOT Analysis to obtain a development strategy for the Sangkumpal Bonang Market. The results of the study show that there are 4 development strategies for the Sangkumpal Bonang Market, namely the aspect of space utilization, economic aspect, SWOT analysis and management aspec